(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article addresses memories and reflections on the language of circus clowns, based on the author’s experience as a member of the Brazilian company Circo Udi Grudi, investigating possible contributions to the pedagogy of performing arts today.